2010
DOI: 10.1097/acm.0b013e3181f53273
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Medical Students How to Teach: A National Survey of Students-as-Teachers Programs in U.S. Medical Schools

Abstract: Formal SAT programs exist for 43 of 99 U.S. medical school respondents. Such programs should be instituted in all schools that use their students as teachers. National teaching competencies, best curriculum methods, and best methods to conduct skills reinforcement need to be determined. Finally, the SAT programs' impacts on patient care, on selection decisions of residency directors, and on residents' teaching effectiveness are areas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(162 citation statements)
references
References 13 publications
5
154
0
3
Order By: Relevance
“…This form of teaching and learning (different teaching sessions spread over weeks with feedback from the instructor) has been described as the most effective method for teaching basic technical skills 28 . However, the time and the number of faculty surgeons available for this form of training is reduced 28 ; the use of non-surgeon skills coaches 39 , trained students (students as teachers) 40,41 or surgical residents 42 as instructors can alleviate these limitations of the method.…”
Section: Discussionmentioning
confidence: 99%
“…This form of teaching and learning (different teaching sessions spread over weeks with feedback from the instructor) has been described as the most effective method for teaching basic technical skills 28 . However, the time and the number of faculty surgeons available for this form of training is reduced 28 ; the use of non-surgeon skills coaches 39 , trained students (students as teachers) 40,41 or surgical residents 42 as instructors can alleviate these limitations of the method.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be promoted by participation in formal students-as-teachers programs, which as of 2010 were offered by 43% of medical schools. 19 Better still is the continuity provided when a student track is integrated with a medical school SC in medical education. In doing so, the annual conference student track can become part of a comprehensive model to support students in their journey toward a medical education career.…”
Section: Personal Success Experiencementioning
confidence: 99%
“…In a survey of US medical schools, 43 of 99 respondents indicated that they offered a formal "student-as-teachers" training program. 6 To ensure continued success in hierarchical pharmacy teaching, formal clinical teaching programs will need to be incorporated earlier in the pharmacist training curriculum.…”
Section: Discussionmentioning
confidence: 99%